Early MRI versus conventional management in the detection of occult scaphoid fractures: what does it really cost? A rural pilot study. Issue 1 (18th January 2016) - Kelson, Tamika; Davidson, Robert; Baker, Tim
Abstract: Introduction: To compare the cost‐effectiveness and patient impact between acute magnetic resonance imaging (MRI) management and conventional management in the diagnosis of occult scaphoid fractures in a rural setting. Methods: Consecutive patients presenting to a rural emergency department (ED) with a suspected scaphoid fracture were randomly assigned to either conventional management (6) or acute MRI management (10) (3 patients were excluded from the study analysis). All healthcare costs were compared between the two management groups and potential impacts on the patients' pain, mobility and lifestyle were also measured. Results: There were no significant differences between the two groups at baseline. There was one (10%) scaphoid fracture in the MRI group and none in the conventional group ( P  = 0.42). A larger proportion of other fractures were diagnosed in the MRI group (20% (2) vs. 16.7% (1), P  = 0.87), as well as less clinic attendances (1 (0–2.25) vs. 4 (2.25–5)) and diagnostic services (1 (1–1.25) vs. 2 (1–3)). Median management costs were $485.05 (AUD) (MRI) and $486.90 (AUD) (conventional). The MRI group had better pain and satisfaction scores as well as less time of immobilisation, treatment and time off work. Conclusion: MRI dramatically reduces the amount of unnecessary immobilisation, time of treatment and healthcare usage in a rural setting. The two protocols are suggested to be equivalent financially. When potential societal costs, the amount of unnecessary immobilisation, low prevalence of true fractures and patient satisfaction are considered, acute MRI should be the management technique of choice. Further studies are still required to assess the best method for managing bone bruise within the scaphoid. Abstract : This study compared the cost‐effectiveness and patient impact between acute magnetic resonance imaging (MRI) management and conventional management in the diagnosis of occult scaphoid fractures in a rural setting. MRI dramatically reduces the amount of unnecessary immobilisation, time of treatment and healthcare usage in a rural setting. When potential societal costs, the amount of unnecessary immobilisation, low prevalence of true fractures and patient satisfaction are considered, acute MRI should be the management technique of choice.